High yield synthesis of propanal from methane and air - Green, M; Tsang, S; Vernon, P; York, A (Baltzer Science Publishers, Baarn/Kluwer Academic Publishers, 1992)
High yield synthesis of propanal from methane and air can be obtained in a single pass at atmospheric pressure. Three catalytic processes are combined to give 13% yield of propanal based on total methane input. Ethene is made from the oxidative coupling reaction and carbon monoxide and hydrogen is generated from partial oxygenation of methane. These gases are combined and passed to a hydroformylation catalyst to give liquid propanal. The unreacted methane is inert in the hydroformylation stage, while oxygen deactivates the catalyst readily. The results imply that propanal can be obtained, in good yield, from methane and air provided that total oxygen conversion is achieved. The yield of propanal from the three combined processes can be substantially higher than that of ethene from the oxidative coupling reaction. Thus, higher yields of a condensible and oxygenated product are obtained. © 1992 J.C. Baltzer A.G. Scientific Publishing Company.